1997
DOI: 10.1016/s1078-5884(97)80188-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to cardiolipin may increase the risk of failure of peripheral vein bypasses

Abstract: Antibodies to cardiolipin were identified in 9% of patients undergoing infrainguinal vein bypass surgery and appeared to be associated with increased risk of bypass failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Mean graft patency for occluded lower limb procedures was 17 months in patients with APS and 50 months in those without. Nielsen et al 19 reported the results of 80 patients undergoing infrainguinal vein bypass surgery. Nine percent of patients had evidence of anticardiolipin antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Mean graft patency for occluded lower limb procedures was 17 months in patients with APS and 50 months in those without. Nielsen et al 19 reported the results of 80 patients undergoing infrainguinal vein bypass surgery. Nine percent of patients had evidence of anticardiolipin antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic variables that might associate with graft stenosis are lipoprotein (a), smoking and plasma fibrinogen, 25 hyperhomocystinemia, 26,27 and antibodies to cardiolipin. 28 The importance of vein quality has been also studied. The hypothesis of preimplantation morphologic changes in the saphenous vein as an etiologic factor of vein graft stenosis is disputed.…”
Section: Discussionmentioning
confidence: 99%
“…Graft thrombosis occurred in 57% of patients with an Anticardiolipin antibody compared to 30% (23/77) of those without. The overall primary patency at 6 months was even lower with 14% in those with Anticardiolipin antibodies compared to 57% in those without ðp ¼ 0:03Þ: 28 Sampram et al suggested that a factor V Leiden mutation was associated with a doubled rate of failure for infrainguinal procedures both at 1 month and 1 year (37% vs. 22% and 46% vs. 27%) but this was not statistically significant (p ¼ 0:15 and 0.09, respectively). 17 The recent publication by Curi et al reports that patients with hypercoagulability were more likely to have undergone prior revascularisation than patients deemed 'normal'.…”
Section: Thrombophilia and Vascular Riskmentioning
confidence: 98%